Analysis of the Local Potential of the Balik Tribe Community as a Sustainable Development Plan in the Capital City of Nusantara: Analisis Potensi Lokal Masyarakat Suku Balik Sebagai Rencana Pembangunan Berkelanjutan di Ibu Kota Nusantara - A. Ismail Lukman; Zulkifli Abdullah; Nur Wahitdah; Kristina Oktaviani Bua (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The development of the Indonesian Capital City (IKN) as the new center of government in Indonesia has brought significant changes to the lives of local communities, including the Balik Tribe. This study aims to analyze the impact of IKN development on the social, cultural, and economic aspects of the Balik Tribe community, as well as to identify local potential that can be developed as an adaptation strategy. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that IKN development has a positive impact in the form of increased economic access, the opening of employment opportunities, and opportunities for business development based on local potential. However, there are also negative impacts, such as threats to the preservation of cultural identity, limited access to resources, and potential marginalization due to competition with newcomers. The Balik Tribe has various local potentials, including cultural wisdom, natural resources, and the ability to adapt economically through business diversification, which can be important capital in facing these changes. Therefore, systematic support from the government and stakeholders is needed through empowerment programs, training, and protection of indigenous peoples' rights to ensure the sustainability and welfare of local communities amidst the IKN development.